A new species of Megadineura Malaise (Hymenoptera: Tenthredinidae) and a key to the known species of the genus - Wei, Meicai; Nie, Haiyan (Zootaxa, 2008)
Megadineura leucotarsis Wei, a new species of Nematinae (Hymenoptera, Tenthredinidae) from China is described. The genus Megadineura Malaise, 1931 is redescribed and a key to known species is provided. The difference between Megadineura and Mesoneura Hartig, 1837, Renonerva Wei & Nie, 1998, Katsujia Togashi, 1964 is also discussed briefly. The type specimens of the new species are deposited in the Insect Collection of Central South University of Forestry and Technology, China.